Study on synthesizing mullite with bauxite tailing - Liu Dongfang; Liu Wenkai; Xue Baoda; Zhang Zhihao; Huang Liangliang; Ma Xiangdong (矿业科学学报, 2016)
To enhance the efficient utilization of bauxite tailings，the mullite was synthesized by bauxite tailings in molybdenum wire furnace at 1 550℃ and 1 650℃ for 4 h.The sintered samples were analyzed by X-ray diffraction(XRD)，scanning electron microscopy(SEM)and energy dispersive spectrometry(EDS).The content of mullite was determined by TOPAS.The results indicated that the mullite was in high purity and well growth.The mullite was long column in morphology，alternating each other.As the temperature increased，the crystal profile of mullite was much more clear and the content of mullite increased slightly.